Vaccinations in patients with inflammatory bowel disease. Issue 12 (December 2021) - Macaluso, Fabio Salvatore; Liguori, Giuseppina; Galli, Massimo
Abstract: Treatment of inflammatory bowel disease (IBD) frequently requires administration of immunosuppressive therapies, which increases susceptibility to a number of infectious pathogens. However, many infections can be prevented by correct and appropriate utilization of vaccinations. While several guidelines have been published on vaccination schedules in patients with IBD, vaccination rates remain suboptimal and even lower than those in the general population. This is due to many factors including poor awareness of the importance of vaccines by gastroenterologists and general practitioners as well as potential prejudices of patients regarding the safety and benefits of vaccines. With the aim of increasing awareness about the key role of immunization in the management of patients with IBD, the present review examines the existing literature relating to the main vaccinations and their application in these patients. We also summarize current evidence in order to provide clinicians with an easy source of reference for the principal recommendations for prevention of infectious diseases in patients with IBD. In addition, the recommendations about traveling for IBD patients are briefly explored. Lastly, since it is important for gastroenterologists to be aware of recommendations on vaccination, we recommend implementing educational programs to ensure compliance with current guidelines.